Effect of different inorganic phosphorus sources on growth performance, digestibility, retention efficiency and discharge of nutrients in rainbow trout (Oncorhynchus mykiss) - Morales, Gabriel Alejandro (2018)
This study aims to evaluate the effect of different sources of inorganic phosphate, monosodium phosphate (MSP), monocalcium phosphate (MCP) and monoammonium phosphate (MAP), included in a diet for rainbow trout, on growth performance, nutrient digestibility, nutrient retention efficiency and discharge of nutrients to the water. Juvenile rainbow trout (Oncorhynchus mykiss) with an initial weight of 120 g were fed for 56 days four experimental diets: basal diet containing 430 g kg−1 protein, 210 g kg−1 lipids and 6.7 g kg−1 total phosphorus (P) (Control), and three experimental diets consisting in the basal diet plus 4 g P kg−1 from MSP, MCP and MAP, respectively. Both MSP and MAP resulted in higher levels of P apparent digestibility (≈90%) compared to MCP (70%), increasing the dry matter digestibility of the nutrient in the feed. The retention efficiency of P in fish tissues was increased by nearly 15% units over the Control when MSP and MAP were used as P supplement, whereas in agreement with the lower digestibility observed in MCP, P retention efficiency from this phosphate source was lower than the other sources. Total P discharge to the water was similar for MSP, MCP and MAP (4.12–4.58 g kg−1 BW fish gain). However, fish fed with MCP showed higher solid/particulate P discharge to the water through faeces due to the lower digestibility of this P–source within the gut of the fish. Among the phosphate salts evaluated, fish fed MSP and MCP did not show differences for soluble or solid N discharged fractions. However, fish fed the diet supplemented with MAP released a higher amount of non–protein N fraction to the water, probably as undigested ammonium through the faeces released by fish.